Siblinghood and rewriting of the myth of Isis and Osiris in contemporary Spanish literature (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2021)
The purpose of this article is to analyze the updating of the myth of Isis and Osiris in three works of Contemporary Spanish Literature, «Balada de un día de julio» (1921) by Federico García Lorca, «Pantomima» (1995) by Manuel Mantero and «El hechizo de Iris» (1999) by José María Merino. To carry out this study, concepts such as mytheme from myth criticism or ideal intertext will be used. Beyond the hypertextuality between the first written versions of the myth and these contemporary versions, the study shows how in contemporary texts the value of the siblinghood that sustains the myth of Isis and Osiris endures and is amplified.
Keywords: Isis and Osiris; siblinghood; update the myth; hypertextuality; myth criticism